# Why is this proof of $i = -1$ wrong? [closed]

I know that $-7^2 = -49$

Therefore $\sqrt{-49} = -7$

Because $\sqrt{-1} = i$ we can then expand it to $\sqrt{-49} = -7 = 7i$

And therefore $-7 = 7i$, divide both sides by 7 and you get

$-1 = i$

And I know that is not true, because $i = \sqrt{-1}$. What is wrong with my proof?

## closed as off-topic by Did, kingW3, Miha Habič, Olivier Bégassat, user99914 May 11 '15 at 0:59

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Did, kingW3, Miha Habič, Olivier Bégassat
If this question can be reworded to fit the rules in the help center, please edit the question.

• $\sqrt{-49}\ne -7$ – Dr. Sonnhard Graubner May 10 '15 at 15:16
• Where to begin.... – Alec Teal May 10 '15 at 15:16
• Do none of the many similar (answered) questions on site address your problem? – Andrew D. Hwang May 10 '15 at 15:16
• @user86418 I call it "upvote whoring" - if you ask a question accessible to people on the other SE sites they'll come here and be like "THIS - this is a fine question!" – Alec Teal May 10 '15 at 15:18
• @quapka I was teasing you because you said " @ AlecTeal I think i=−7, not that it matters.." <-- claiming that YOU think this :P – Alec Teal May 10 '15 at 15:30

At risk of sounding tart, it's easier to say what's right with the proof:

• $-7^{2} = -49$ is true (because with normal precedence of operations "$-7^{2}$" means "$-(7^{2})$".

• $\sqrt{-1} = i$ is fine as notation, but will reliably start an argument in some quarters on Math.SE. (What vexes people is that $\sqrt{\ }$ is a function in the sense understood by The General Public only if the radicand is a non-negative real number, and $-1$ is not a non-negative real number.)

What's wrong:

• $-(7^{2}) \neq (-7)^{2}$, so "Therefore $\sqrt{-49} = -7$" doesn't follow.

• On using $\sqrt{-1} = i$ to expand $\sqrt{-49}$, two falsehoods get daisy-chained, $\sqrt{-49} = -7$ and $-7 = 7i$. Ironically, the combined effect, "$\sqrt{-49} = 7i$" is correct in the sense that $(7i)^{2} = -49$. This shows that in mathematics, two wrongs (sometimes) do make a right.

• If we include errors of style, the introduction of $7$ into the proceedings does nothing to clarify. The entire proof could have been reduced to one erroneous step:

I know that $-1^{2} = -1$.

Therefore $-1 = i$.

What is wrong with my proof?

And then the sign error would have been apparent: $-1 = -1^{2} = -(1^{2}) \neq (-1)^{2} = 1$.

The real moral is the same as with debugging code: Always strive to reduce a contradiction to the smallest and/or simplest problematic situation possible.

The meaning of the first line is $-(7^2)=-49$, not $(-7)^2=-49$, the second one is wrong.

Therefore, what comes after therefore is wrong.

• "Therefore, what comes after therefore is wrong." Well, actually, what comes after therefore could be true. :-) – Did May 10 '15 at 15:45

There are several mistakes that I notice. First off, $\sqrt{-49}\neq -7$, since $(-7)^2 = 49,$ not $-49$ (also note that $-7^2 \neq (-7)^2$).

Also, it is very dangerous to say that $i = \sqrt{-1},$ without full understanding that the square root is multi-valued. That is, since $(-i)^2 = i^2 = -1$, we also have that $\sqrt{-1} = -i$. What you do know, for sure, is that $i^2 = -1$.

You confused $-x^2$ with $(-x)^2$.

• What? $\sqrt{-7}\ne7i$, last time I checked. It equals $i\sqrt7$. – Akiva Weinberger May 10 '15 at 15:24
• @columbus8myhw Oops, thanks for catching my error. – Jimmy360 May 10 '15 at 15:28